Prozaiczna codzienność superbohaterów, czyli analiza komiksowej serii Karla Ferdona - Justyna Czaja (Załącznik Kulturoznawczy)
The article discusses a parody comic series by Chilean cartoonist Karlo Ferdon which depicts American superheroes in prosaic day-to-day situations. The author shows how placing iconic pop culture characters in an unexpected context can lead to their deconstruction and demythologization.